New Insights into ECCU's Tourism Sector Competitiveness - Ghazanchyan, Manuk (IMF Working Papers; Working Paper ;, 2019)
Tourism has become the main driver of economic growth and employment and the most important source of income in the ECCU. Preserving and, possibly, enhancing the competitiveness of the tourism product is key for these countries. Unfortunately, the evidence shows that tourism arrivals to the ECCU have been declining slightly while global demand for tourism is on the rise. The objective of this paper is to study the structural determinants of competitiveness for the ECCU, defined as the relative cost advantage over other touristic regions (Di Bella, Lewis, and Martin 2007). Using a gravity model, we show that proximity to North American and European markets is indeed an important competitive advantage for the ECCU. However, despite this advantage, and, in some cases, specialization in high-end tourism, regression analysis shows that arrivals to the ECCU are sensitive to relative prices. Our simulations show that mitigating supply-side constraints would improve the ECCU's competitiveness and allow the region to regain global market shares.